The unexpected long period of elevated CH4 emissions from an inundated fen meadow ended only with the occurrence of cattail (Typha latifolia) - Antonijević, Danica (Global change biology, 2023)
© 2023 The Authors. Global Change Biology published by John Wiley & Sons Ltd.